Assessing Eclectic Language Training for Children in Yogyakarta - Sukci, L. Bening Parwita; Kristanto, Ignatius Indra (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2024)
This research examines how well eclectic language teaching methods can improve the confidence and English language ability of poor children in Yogyakarta. The study utilized qualitative methods for gathering data, such as participant observation, to monitor the advancement of participants over a prolonged duration. Children from a variety of socioeconomic situations enrolled in elementary school participated in an English language training program run by the Parish of St. Antonius Padua, Kotabaru. The program used a variety of strategies, such as narrative and gamification, to provide interesting learning opportunities. The findings show that both narrative and gamification were successful in raising participants’ self-confidence and English language proficiency. Particularly for younger pupils, gamification exercises like coloring, drawing, and quizzes encouraged active involvement and language recall. Grammar and vocabulary growth were aided by storytelling sessions.